Direct Role of Structural Dynamics in Electron-Lattice Coupling of Superconducting Cuprates - Carbone, F; D -S Yang; Giannini, E; Zewail, A H (arXiv.org, 2009)
The mechanism of electron pairing in high-temperature superconductors is still the subject of intense debate. Here, we provide direct evidence of the role of structural dynamics, with selective atomic motions (buckling of copper-oxygen planes), in the anisotropic electronlattice coupling. The transient structures were determined using time-resolved electron diffraction, following carrier excitation with polarized femtosecond heating pulses, and examined for different dopings and temperatures. The deformation amplitude reaches 0.5 % of the c-axis value of 30 A when the light polarization is in the direction of the copper-oxygen bond, but its decay slows down at 45 degrees. These findings suggest a selective dynamical lattice involvement with the anisotropic electron-phonon coupling being on a time scale (1 to 3.5 ps depending on direction) of the same order of magnitude as that of the spin exchange of electron pairing in the high-temperature superconducting phase.